2013
DOI: 10.1890/11-2120.1
|View full text |Cite
|
Sign up to set email alerts
|

Why do mixotrophic plants stay green? A comparison between green and achlorophyllous orchid individuals in situ

Abstract: Abstract. Some forest plants adapt to shade by mixotrophy, i.e., they obtain carbon both from photosynthesis and from their root mycorrhizal fungi. Fully achlorophyllous species using exclusively fungal carbon (the so-called mycoheterotrophic plants) have repeatedly evolved from such mixotrophic ancestors. However, adaptations for this evolutionary transition, and the reasons why it has happened a limited number of times, remain unknown. We investigated this using achlorophyllous variants (i.e., albinos) spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(132 citation statements)
references
References 97 publications
4
127
1
Order By: Relevance
“…However, the patterns observed here of 13 C depletion in evergreen sclerophyllous PMH Ericaceae relative to deciduous PMH Orchidaceae do not fit with the general tendency of sclerophyllous plants towards lower stomatal conductance and therefore greater 13 C enrichment (Larcher, 2003). Furthermore, for non-photosynthetic FMH albino individuals of the orchid Cephalanthera damasonium, a significantly higher stomatal conductance and simultaneously higher 13 C enrichment than in PMH individuals has been found (Julou et al, 2005;Roy et al, 2013). Consequently, systematic differences in stomatal conductance are also unlikely to be responsible for the differences in 13 C enrichment found for FMH and PMH plants of the Orchidaceae and Ericaceae.…”
Section: Drivers Of Nitrogen Concentrations Among Plant Families and contrasting
confidence: 90%
See 1 more Smart Citation
“…However, the patterns observed here of 13 C depletion in evergreen sclerophyllous PMH Ericaceae relative to deciduous PMH Orchidaceae do not fit with the general tendency of sclerophyllous plants towards lower stomatal conductance and therefore greater 13 C enrichment (Larcher, 2003). Furthermore, for non-photosynthetic FMH albino individuals of the orchid Cephalanthera damasonium, a significantly higher stomatal conductance and simultaneously higher 13 C enrichment than in PMH individuals has been found (Julou et al, 2005;Roy et al, 2013). Consequently, systematic differences in stomatal conductance are also unlikely to be responsible for the differences in 13 C enrichment found for FMH and PMH plants of the Orchidaceae and Ericaceae.…”
Section: Drivers Of Nitrogen Concentrations Among Plant Families and contrasting
confidence: 90%
“…We identified 21 publications suitable for our study published between 2003 and 2015 and added one further so far unpublished data set (Table 1). We explicitly excluded from our data set investigations for which the sampling design did not allow calculation of enrichment factors (Trudell et al, 2003) or for which C and N isotope abundance was affected by experimental manipulations [shading and trenching (Hynson et al, 2012); fungicide application (Bellino et al, 2014); defoliation (Gonneau et al, 2014)], by investigation of chlorophyll concentration gradients (Stöckel et al, 2011) or by investigation of different developmental stages (Roy et al, 2013;Gonneau et al, 2014). We did include data from mutant achlorophyllous (albino) orchids that are fully mycoheterotrophic.…”
Section: Data Compilationmentioning
confidence: 99%
“…Recent studies have shown that, in partially mycoheterotrophic orchids, carbon derived from mycorrhizal fungi mostly supports young spring shoots and below‐ground organs, whereas carbon originating from photosynthesis contributes most to sexual reproduction (Gonneau et al, ; Lallemand et al, ; Suetsugu, Ohta, & Tayasu, ). These results may explain why albino plants fail to produce similar levels of seeds than green plants, but show the same survival rates (Lallemand et al, ; Roy et al, ). Using fungicides, Bellino et al () were able to eliminate the mycorrhizal fungi associating with the partially mycoheterotrophic orchid Limodorum abortivum without impairing fruit production, supporting the idea that carbon derived from fungi contributes little to sexual reproduction.…”
Section: Discussionmentioning
confidence: 90%
“…Detailed physiological measurements and long‐term observations in mixed populations of the woodland orchid Cephalanthera damasonium have shown that albinos are in general less fit than their green counterparts. Albinos displayed more frequent shoot drying at fruiting, possibly due to stomatal dysfunctions, had a lower basal metabolism, showed increased sensitivity to pathogens and herbivores, had higher dormancy and showed signs of maladapted sprouting, and produced, probably due to the previous differences, fewer seeds, which in turn had a lower germination capacity (Roy et al, ). When all fitness costs were added, albinos were estimated to have a 10 3 × fitness reduction, compared to green plants, suggesting that a successful transition to full mycoheterotrophy is unlikely to occur from albino plants.…”
Section: Evidence For Mycorrhizal Shifts During the Evolution Towardsmentioning
confidence: 99%
“…Full mycoheterotrophy evolved repeatedly and different adaptations were likely involved in this process (Roy et al . ). Notably, in the orchid family only ca .…”
Section: Discussionmentioning
confidence: 97%